FAKTOR EKONOMI MAKRO TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Yubiharto Yubiharto; Siti Mauliyah; Walid Rudianti (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2021)
ABSTRACT Basically, when inflation, interest rates and exchange rates increase, the Composite Stock Price Index will decrease. The problem in this study is that in fact inflation, interest rates and exchange rates have increased, in fact the Composite Stock Price Index has increased. This study aims to determine the effect of inflation, interest rates and exchange rates on the Composite Stock Price Index on the Indonesia Stock Exchange. This type of research is associative, with a quantitative approach. This study takes all data in time series including inflation, interest rates, exchange rates and the Composite Stock Price Index for the 2015-2019 period. The sample in this study used a saturated sampling of 60 samples. The analysis technique used is multiple linear regression, classical assumption test and hypothesis testing. The partial test results show that inflation and exchange rates have no effect on the Composite Stock Price Index, interest rates have a significant negative effect on the Composite Stock Price Index. Simultaneous test results show that the variables of inflation, interest rates and exchange rates have a significant effect on the Composite Stock Price Index. The value of the coefficient of determination in this study is 0.451. This means that the ability of the independent variable to explain the dependent variable is 45.1%, while the rest is explained by other variables not included in this study.